Association between Lipoprotein(a) and diabetic nephropathy in patients with type 2 diabetes - Li, Meng; Wang, Yanjun; Yao, Qianqian; Liang, Qian; Zhang, Yuanyuan; Wang, Xin; Li, Qian; Qiang, Wei; Yang, Jing; Shi, Bingyin; He, Mingqian (Frontiers in Endocrinology, 2024)
Background Diabetic nephropathy (DN) is one of the most prevalent and severe microvascular complications of type 2 diabetes (T2DM). However, little is currently known about the pathogenesis and its associated risk factors in DN. The present study aims to investigate the potential risk factors of DN in patients with T2DM. Methods A total of 6,993 T2DM patients, including 5,089 participants with DN and 1,904 without DN, were included in this cross-sectional study. Comparisons between the two groups (DN vs. non-DN) were carried out using Student’s t-test, Mann-Whitney U-test, or Pearson’s Chi-squared test. Spearman’s correlation analyses were performed to assess the correlations of serum lipids and indicators of renal impairment. Logistic regression models were applied to assess the relationship between blood lipid indices and the presence of DN. Results T2DM patients with DN were older, and had a longer duration of diagnosed diabetes compared to those without DN. Of note, the DN patients also more likely develop metabolic disorders. Among all serum lipids, Lipoprotein(a) [Lp(a)] was the most significantly correlated indicators of renal impairment. Moreover, univariate logistic regression showed that elevated Lp(a) level was associated with an increased risk of DN. After adjusted for confounding factors, including age, gender, duration of T2DM, BMI, SBP, DBP and lipid-lowering drugs usage, Lp(a) level was independently positively associated with the risk of DN [odds ratio (OR):1.115, 95% confidence interval (CI): 1.079-1.151, P=6.06×10-11]. Conclusions Overall, we demonstrated that serum Lp(a) level was significantly positively associated with an increased risk of DN, indicating that Lp(a) may have the potential as a promising target for the diagnosis and treatment of diabetic nephropathy.